Pengaruh Pemberian Bifosfonat terhadap Pasien dengan Fraktur Tulang Panjang Pasca Open Reduction Internal Fixation (ORIF) - Ijong, Jessie I.; Sunaryo, Haryanto; Rawung, Rangga (Universitas Sam Ratulangi, 2024)
Abstract: Clinical, radiographic, and laboratory tests can be used to evaluate bone healing of fractured bone. This study aimed to analyze the impact of bisphosphonate medication on the prognosis of patients receiving open reduction internal fixation (ORIF) for long bone fractures. This was a randomized controlled trial study. Information was gathered prospectively, meaning that osteocalcin level was checked on each patient who fulfilled the study's eligibility requirements. The non-parametric Mann-Whitney test or the bivariate T test was the employed statistical test. Linear regression test was applied to multiple variables. The results showed that the average age of men and women was 36 years, with a 6:4 gender ratio. Patients were divided into two groups, namely the bisphosphonate and the control groups The average pre-ORIF osteocalcin level was 12 ng/mL. In comparison to controls, patients taking oral bisphosphonates had a slightly higher mean (12.9 vs 11.5 ng/mL; p=0.017). This difference maintained following ORIF, when the mean osteocalcin level in the bisphosphonate group increased to roughly 20 ng/mL whereas it was only 16 ng/mL in the control group (p=0.002). The callus index of the patients pre-ORIF did not significantly differ from the mediolateral or anteroposterior aspects. After ORIF, differences started to be noticed where both methods of measuring the callus index produced identical results for patients on oral bisphosphonates (median 1.2) and controls (median 1.1). In conclusion, administration of sodium bisphosphonate has an influence on patients experiencing long bone fractures and open reduction internal fixation (ORIF). Keywords: long bone fracture; osteocalcin; callus; bisphosphonate Abstrak: Penyembuhan tulang (union) dapat dinilai dari pemeriksaan klinis, radiologis, dan laboratorium. Penelitian ini bertujuan untuk mengevaluasi pengaruh pemberian bifosfonat terhadap luaran pasien fraktur tulang panjang pasca open reduction internal fixation (ORIF). Jenis penelitian ialah studi randomized controlled trial. Informasi dikumpulkan secara prospektif, yaitu setiap pasien yang memenuhi kriteria penelitian diambil datanya dan diperiksa kadar osteokalsin. Uji bivariat yang digunakan ialah uji T atau uji non parametrik Mann–Whitney, serta uji multivariat menggunakan regresi linear. Hasil penelitian mendapatkan rasio laki-laki : perempuan sebesar 6:4 dengan rerata usia 36 tahun, yang dibagi atas kelompok bifosfonat dan kelompok kontrol. Kadar osteokalsin pra ORIF secara umum sekitar 12 ng/mL. Nilai rerata tersebut sedikit lebih tinggi pada kelonmpok bifosfonat dibandingkan kontrol (12,9 vs 11,5 ng/mL; p = 0,017). Perbedaan tersebut terus bertahan pasca ORIF di mana rerata kadar osteokalsin mencapai sekitar 20 ng/mL pada kelompok bifosfonat sedangkan kontrol 16 ng/mL (p=0,002). Indeks kalus para pasien sampel pra ORIF relatif tidak berbeda baik dilihat dari aspektus anteroposterior maupun mediolateral. Perbedaan mulai terdeteksi pasca ORIF di mana kedua pendekatan penilaian indeks kalus tersebut memberikan hasil yang sama untuk pasien dengan bifosfonat oral (median 1,2) maupun kontrol (median 1,1). Simpulan penelitian ini ialah pemberian natrium bifosfonat memiliki pengaruh terhadap pasien fraktur tulang panjang dengan open reduction internal fixation (ORIF). Kata kunci: fraktur tulang panjang; osteokalsin; kalus; bifosfonat